1968
DOI: 10.1113/jphysiol.1968.sp008508
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic receptors at sympathetic preganglionic nerve terminals

Abstract: SUMMARY1. In the paravertebral sympathetic chain of bullfrogs, some part of the preganglionic nerve located within the ganglion was depolarized transiently when acetylcholine (ACh) was directly applied to the ganglion, particularly in the presence of an anticholinesterase (anti-ChE). The axonal part of the preganglionic nerve, on the other hand, showed no detectable depolarization following direct application of ACh (with anti-ChEs) to the interganglionic nerve trunk.2. The ACh depolarization was markedly depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…This finding is difficult to reconcile with the proposed cholinergic recurrent excitatory pathway to motoneurones (Matsurra, 1971), although it is conceivable that recording from the spinal roots might not have detected small responses generated in the motoneurone dendrites. The fact that unmyelinated nerve terminals of the primary afferents are unresponsive to acetylcholine and carbachol suggests that the acetylcholine sensitivity observed in some unmyelinated fibres and terminals (Armett & Ritchie, 1960;Hubbard, Schmidt & Yokota, 1965;Koketsu & Nishi, 1968) does not apply to all nerve fibres.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is difficult to reconcile with the proposed cholinergic recurrent excitatory pathway to motoneurones (Matsurra, 1971), although it is conceivable that recording from the spinal roots might not have detected small responses generated in the motoneurone dendrites. The fact that unmyelinated nerve terminals of the primary afferents are unresponsive to acetylcholine and carbachol suggests that the acetylcholine sensitivity observed in some unmyelinated fibres and terminals (Armett & Ritchie, 1960;Hubbard, Schmidt & Yokota, 1965;Koketsu & Nishi, 1968) does not apply to all nerve fibres.…”
Section: Discussionmentioning
confidence: 99%
“…If the rat superior cervical ganglion is arranged in the sucrose-gap so that the recorded potential differences arise between the proximal pole of the ganglion and the cervical sympathetic trunk, depolarizations induced on superfusion with ACh are thought to arise mainly in the preganglionic nerve terminals (Koketsu & Nishi, 1968). This experimental arrangement is shown diagrammatically in Figure 8.…”
Section: Possible Presynaptic Actions Of S-htmentioning
confidence: 99%
“…It is now well established that ACh and ACh-like agents initiate antidromicallypropagated discharges in certain nerve terminals (for example Masland & Wigton, 1940;Feng & Li, 1941;Riker, Roberts, Standaert & Fujimori, 1957;Randic & Straughan, 1964), and that ACh can depolarize non-myelinated nerve fibres (Armett & Ritchie, 1960) including preganglionic sympathetic nerve terminals (Koketsu & Nishi, 1968). Koelle (1961Koelle ( , 1962 suggested that the presynaptic effect of ACh is an integral part of the physiology of synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%